DEVELOPMENT OF HIGHER EDUCATION IN UZBEKISTAN: HISTORY, CHALLENGES AND PROSPECTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the key changes, reforms, stages of development, problems, and solutions in the higher education system of Uzbekistan, particularly in the Bukhara region, during the years of independence. The article also provides detailed information on the formation processes and future prospects of the national model of higher education using the example of the Bukhara region.